2016
DOI: 10.1007/s00345-016-1828-0
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up after focal therapy in renal masses: an international multidisciplinary Delphi consensus project

Abstract: PurposeTo establish consensus on follow-up (FU) after focal therapy (FT) in renal masses. To formulate recommendations to aid in clinical practice and research.MethodsKey topics and questions for consensus were identified from a systematic literature research. A Web-based questionnaire was distributed among participants selected based on their contribution to the literature and/or known expertise. Three rounds according to the Delphi method were performed online. Final discussion was conducted during the “8th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In our opinion, it is crucial to investigate the clinical efficacy of IRE in renal tumors to serve as a solid base for a large randomized trial. We aim to determine the clinical effect of IRE by assessing the presence of enhancement on cross-sectional imaging during follow-up as it is advised in thermal ablation [30]. Whereas IRE is a novel ablation technology, posttreatment radiological features in CT scan or MRI are still ill-defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, it is crucial to investigate the clinical efficacy of IRE in renal tumors to serve as a solid base for a large randomized trial. We aim to determine the clinical effect of IRE by assessing the presence of enhancement on cross-sectional imaging during follow-up as it is advised in thermal ablation [30]. Whereas IRE is a novel ablation technology, posttreatment radiological features in CT scan or MRI are still ill-defined.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that biopsy during the follow-up targeting the ablation zone may contribute to histopathological confirmation, it would have brought additional burden in a fragile population and would not have been an irrefutable proof of complete ablation. Therefore, as provided by the consensus that ablation success in kidney tumors is assessed by radiological characteristics [30], success in our study will be assessed exclusively based on radiological features.…”
Section: Discussionmentioning
confidence: 99%
“…The initiative followed a rigorous, systematic methodology with multiple iterations to achieve a consensus. We recruited a large number of multidisciplinary research experts and achieved similar response rates to those observed in other Delphi surveys performed in a urological setting [15,16,24,25]. The response rate increased during subsequent survey iterations.…”
Section: Methodological Considerationsmentioning
confidence: 96%
“…The oncological outcomes (persistence, local recurrence, systemic progression, overall [OS], disease-specific [DSS], and local recurrence-free survival [RFS]) were analysed for patients with biopsy confirmed RCC ( n = 131). Persistence was defined as residual tumour (contrast enhancement in the ablation site) on first imaging (at 3 months), whereas local recurrence was defined as any contrast enhancement on follow-up imaging at the site of ablation after initial imaging without contrast enhancement [ 7 ]. The OS was defined as the duration from date of LCA to death or 5-year follow-up, with no restriction on the cause of death.…”
Section: Methodsmentioning
confidence: 99%
“…All postoperative imaging for follow-up was interpreted by a board of certified abdominal radiologists with special expertise in focal therapy for kidney cancer. According to the international multidisciplinary Delphi consensus project by Zondervan et al [7], presence of any radiological enhancement at the 3-month radiological follow-up was considered as persistence. A new (after a period of non-enhancement) enhancing or growing lesion, inside or in the margin of the ablated zone was considered local recurrence.…”
Section: Follow-upmentioning
confidence: 99%